The Structural Integrity of Plasmid-Encoded Pgp3 Is Essential for Induction of Hydrosalpinx by Chlamydia muridarum - Huang, Yumeng; Sun, Yina; Qin, Tai; Liu, Yuanjun (Frontiers in Cellular and Infection Microbiology, 2019)
Pgp3 consists of globular N- and C terminal domains connected by a triple-helical coiled-coil middle domain. We demonstrated previously that Pgp3 is required for induction of hydrosalpinx by Chlamydia muridarum. We constructed C. muridarum transformants harboring deletion of the Pgp3 N-terminus (pgp3∆n), C-terminus (pgp3∆c), or middle domain (pgp3∆m). C3H/HeJ and CBA/J mice infected with pgp3∆n or pgp3∆m failed to induce hydrosalpinx in oviduct tissue. However, the pgp3∆c transformant induced mild hydrosalpinx in 20% of C3H/HeJ mice (severity score 0.2 ± 0.6) and in 40% of CBA/J mice (severity score 0.8 ± 1.3). The attenuated pathogenicity of the transformants harboring Pgp3 domain deletions was correlated with impaired in vitro growth and significantly reduced infectivity in the mouse lower genital tract. Moreover, the oviduct tissue of C3H/HeJ and CBA/J mice infected with the Pgp3-domain-deficient transformants displayed less inflammatory cell infiltration. Thus, the structural integrity of plasmid-encoded Pgp3 is essential for induction of hydrosalpinx by C. muridarum.